Association between the risk of heart failure hospitalization and end-stage renal disease with digoxin usage in patients with cardiorenal syndrome: A population-based study - Chang, Kai-Ting; Kuo, Hsuan-Fu; Chang, Yu-Han; Wang, Yu-Tsang; Yang, Lii-Jia; Niu, Sheng-Wen; Kuo, I-Ching; Chen, Yumay; Wen, Zhi-Hong; Hung, Chi-Chih; Chang, Jer-Ming; Lin, Hugo Y.-H (Frontiers in Public Health, 2023)
Background: The management of the coexistence of heart disease and kidney disease is increasingly challenge for clinicians. Chronic kidney disease (CKD) is not only a prevalent comorbidity of patients with heart failure but has also been identified as a noteworthy risk factor for all-cause mortality and poor clinical outcomes. Digoxin is one of the commonest treatments for heart disease. There are few trials investigating the role of digoxin in patients with cardiorenal syndrome (CRS). The aim of this study is to examine the clinical effects of digoxin usage in patients with CRS in a nation-wide cohort. Method: We conducted a population-based study which included 705 digoxin users with CRS; each patient was age, sex, comorbidities, and medications matched with three nonusers who were randomly selected from CRS population. Cox proportional hazards regression analysis was conducted to estimate the effects of digoxin on the incidence of all-cause mortality, congestive heart failure (CHF) recurrence, coronary artery disease (CAD) recurrence, and end stage renal disease (ESRD). Results: The all-cause mortality rate was significantly higher in digoxin users than in nonusers (adjusted hazard ratio [aHR] = 1.26; 95% confidence interval [CI]= 1.09–1.46, p=0.002). In subgroup analysis, there was significantly high mortality in the 0.26-0.75 defined daily dose (DDD) subgroup of digoxin users (aHR= 1.49; 95% CI= 1.23–1.82, p<0.001). And the p for trend was 0.013. With digoxin prescription, the CHF recurrence rate was significantly higher (subdistribution HR (sHR)= 1.17; 95% CI= 1.05–1.30, p=0.004), especially in the >0.75 DDD subgroup (sHR= 1.19; 95% CI= 1.01–1.41, p=0.046), (p for trend= 0.006). The digoxin usage lowered the coronary artery disease (CAD) recurrence in the >0.75 DDD subgroup (sHR= 0.79; 95% CI= 0.63–0.99, p=0.048). In renal function progression, more patients with CRS entering ESRD with digoxin usage (sHR= 1.34; 95% CI= 1.16–1.54, p<0.001). And there was a significantly greater incidence of ESRD in the <0.26 DDD, and 0.26-0.75 DDD subgroups of digoxin users (sHR= 1.32; 95% CI= 1.06–1.66, p=0.015; sHR= 1.44; 95% CI= 1.18–1.75) (p for trend< 0.001). Conclusions: Digoxin should be prescribed with caution to patients with CRS.